Abstracts Writing : A Path for Understanding Academic Text of Mathematics - Misdi, Misdi (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2014)
This is a qualitative study to explore the students' competence in pursuing ofabstract writing among the undergraduate students of Mathematics department. The data were collected through classroom observation and self report. By applying self assignment, small group discussion, and presentation, the students' writing experiences were employed in order to discuss the weaknesses and strengths of the mathematic articles given during class discussion; whereas proof-reading, revising, and supervising were also critically provided. As the results, five classes that were involved in the investigation as the sample shows their abilities in applying their best practices based on the suggested method. The results indicate that the undergraduate students of Mathematics were able to reconstruct their ideas in the form of abstract feature, while the abstract writing method was possibly applied in the course of Mathematics.